ENVIRONMENTAL POLLUTION BY ELECTRONIC WASTE AND THEIR HEALTH CHALLENGES (World Science, 2021)
This article explores the issues of dealing with electrical and electronic departures in different countries and Azerbaijan, as well as the analysis of legal and regulatory acts of these countries in this area and the impact of these departures on people here.Electronic waste is a serious source of danger to the human body and the environment. The preparation of regulatory documents governing the e-waste management system in Azerbaijan is an urgent issue, and for this, the provisions of the legislation adopted in the countries of Eastern Europe can be used.